Ethnic Variation in the Annual Rates of Adult Inflammatory Bowel Disease in Hospitalized Patients in Vancouver, British Columbia - Birinder K Mangat; Chad Evaschesen; Tim Lee; Eric M Yoshida; Baljinder Salh (Canadian Journal of Gastroenterology)
BACKGROUND: There is currently little available information regarding the impact of ethnicity on the clinical features of inflammatory bowel disease (IBD). Migrating populations and changing demographics in Vancouver, British Columbia (BC) provide a unique opportunity to examine the role of ethnicity in the prevalence, expression and complications of IBD.